2009
DOI: 10.4489/myco.2009.37.1.072
|View full text |Cite
|
Sign up to set email alerts
|

Differential Growth Response of Various Crop Species to Arbuscular Mycorrhizal Inoculation

Abstract: To investigate the growth response of various crop species to mycorrhizal inoculation, arbuscular mycorrhizal fungi were applied to Glycine max, Vigna angularis, Senna tora, Hordeum vulgare var. hexastichon. Zea mays, Sorghum bicolor, Allium tuberosum, Solanum melongena, and Capsicum annuum. The biomass of the inoculated crops was measured every two weeks for the 12-week growth period. By measuring biomass, we calculated the mycorrhizal responsiveness of the nine crop species. Among the nine crop species, four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…The findings of this research agree with the report by Eo & Eom (2009) on some vegetable plants and Lu & Wu (2017) on white clover (Trifolium repens) where plants inoculated with AMF showed higher biomass increment. Hoeksema et al (2010) reported that plants colonised by AMF grew larger than those without AMF.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The findings of this research agree with the report by Eo & Eom (2009) on some vegetable plants and Lu & Wu (2017) on white clover (Trifolium repens) where plants inoculated with AMF showed higher biomass increment. Hoeksema et al (2010) reported that plants colonised by AMF grew larger than those without AMF.…”
Section: Discussionsupporting
confidence: 92%
“…The amount of P in the potting medium used in the study was not controlled as the soil was collected from an agricultural field. The source of AMF inoculum added to T2 was from a disturbed forest thus the possibilities that environmental conditions, such as variation in soil P, may have influenced the diversity of AMF taxa causing differences in response by the host plants (Eo & Eom, 2009). Goss et al (2017) also highlighted the impact of past cultural practices that can influence mycorrhizal colonisation.…”
Section: Discussionmentioning
confidence: 99%
“…This was not the case here when legumes were the AM host. While several crop species, including cereals (Zhang et al 2019), generally respond positively to inoculation with AM fungi, this is often less so for cereals (Eo and Eom 2009). Indeed, cereal responses to AM fungi are generally positive but weak, highly crop-specific, and tend to be negative for crops released after the 1950s (Zhang et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, to overcome these drawbacks, most ginseng fields are treated with agricultural chemicals. Recently, both domestic and foreign ginseng growers have begun to focus on sustainable production and clean technology, with a concurrent increase in the use of various helpful fungi for organic and clean farming [ 11 , 12 ].…”
mentioning
confidence: 99%